Corporate Spiritual Responsibility (CSpR): Kontruksi Model CSR berdasarkan Surat Al-Mudassir dan Kitab Tarbiyah Wa Tahdzib - Jannah, Fitriyahtul; Leniwati, Driana (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Purpose: This study aims to construct the model of Corporate Social Responsibility (CSR) based on Surah Al Mudassir and Kitab Tarbiyah Wa Tahdzib in Islamic boarding schools. Method: This research uses a postmodernist-interpretivist paradigm where the research tries to integrate the meaning of each data obtained through interviews and construct a Corporate Social Responsibility (CSR) model based on Surah Al Mudassir and the Kitab of Tarbiyah Wa Tahdzib. Results: Empirically in Islamic boarding schools, it was found that 1) The application of Corporate Social Responsibility (CSR) towards profits is interpreted as sustenance that arises from a sense of sufficiency and gratitude, 2) The application of Corporate Social Responsibility (CSR) towards people is interpreted as charity service. 3) The implementation of corporate social responsibility (CSR) for the planet is interpreted as mutual concern and responsibility. Implications: this study provides implications for accounting science, especially the concept of CSR in a broader context Novelty: This study focuses on the construction of a CSR model that integrates organizational culture, religion and spirituality into a CSR model based on Surah Al Mudassir and Kitab Tarbiyah Wa Tahdzib